The TPACK model as an analysis perspective in the integration of ICTs in education: a state of the art. (2020)
The process of integrating ICTs in education is a phenomenon that has been relatively studied in recent decades. Nevertheless, throughout the last five years, due to the dynamics of what is now called the di gital age, the concern to improve education using new technologies has increased. This chapter aims to analyze the most relevant publica tions on this matter to describe the status quo. The TPACK model is used as an analysis perspective due to its high relevance in integrating ICTs in education. Likewise, the descriptive methodology uses the interpretation levels proposed by Rodríguez Jerez (2019) to carry out a hermeneutic analysis. The results obtained are organized from the area, and the units of convergence are found. The conclusions provide a framework to reflect and understand the current process of integrating ICTs in teaching and learning.